Public Expenditure and National Income: Time Series Evidence from Nigeria - Nwude, E. Chuke; Boloupremo, Tarila (International Journal of Economics and Financial Issues, 2018)
The paper investigates the relationship between national income and government aggregate expenditure in Nigeria by testing the validity of Wagner's law and Keynes's hypothesis for the period between 1970 and 2014. More specifically, by applying time-series analysis, government-spending and national-income variables were found to be non-stationary and cointegrated, thus satisfying a long-run equilibrium condition. In addition, through the application of Granger causality tests to error correction models, unidirectional causality, running from Gross Domestic Product (GDP) to government-expenditure variables, could be established between the variables and, therefore, only Wagner's law was found to be valid in Nigeria's case for the period of study. Keywords: Public expenditure; Wagner's law; causality; unit roots; cointegration JEL Classifications: H5, P44